Rural Banking in India: The role of commercial and regional rural banks in the growth of rural sector in India (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Rural banking in India started since the establishment of banking sector in India. Rural Banks in those days mainly focused upon the agro sector. Today, commercial banks and Regional Rural Banks in India are penetrating every corner of the country are extending a helping hand in the growth process of the rural sector in the country.